2019
DOI: 10.12669/pjms.35.1.366
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis-C and it’s seroconversion in end stage kidney disease patients on maintenance hemodialysis and factors affecting it

Abstract: Objective: To determine frequency of hepatitis-C in dialysis patients at start of hemodialysis, seroconversion from HCV negative to HCV positive over study duration and factors affecting seroconversion. Methods: This descriptive prospective observational study done in dialysis center of DHQ hospital Sheikhupura, Punjab, Pakistan. The study was conducted from October 2016 to October 2017. Data was collected on Performa and later followed prospectively in same cohort of patients. All the patients on mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 13 publications
(13 reference statements)
0
15
0
2
Order By: Relevance
“…The details and main characteristics of the 19 selected studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] are presented in Table 1. Twelve studies had used a cross-sectional research design, while seven studies did not explicitly specify their research design.…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The details and main characteristics of the 19 selected studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] are presented in Table 1. Twelve studies had used a cross-sectional research design, while seven studies did not explicitly specify their research design.…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%
“…Multiple studies have reported the prevalence of HCV infection among hemodialysis patients in Pakistan [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. To the best of our knowledge, no official nationwide survey or national health registry has to date estimated the prevalence of HCV in hemodialysis patients in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…In Pakistan it is common practice to dialyze such patients on separate dedicated machines with separate area and separate staff yet HCV prevalence of 16.4%-61.8 % has been reported from Pakistan. [9][10][11][12][13][14][15] Most of the studies and reviews do not agree with these recommendations, however, in unison recommend universal precautions to control infections. 6,8 Continuous education of dialysis staff for universal infection prevention strategies including hand washing techniques and needle handling with proper disinfection of machines are the only way to curtail the spread of the disease.…”
Section: 5mentioning
confidence: 99%
“…Hussain et al demonstrated a 53.3% seroconversion rate for hepatitis C positive on HD in Lahore. 12 The risk of acquiring these sinister infections on PD is negligible.…”
Section: Number Of Capd Patients In Pakistanmentioning
confidence: 99%